Psychological Drivers of Kindergarten Teacher Performance: A Qualitative Case Study of Motivation in Indonesian Early Childhood Education - Neni Rosmiati (SWATANTRA, 2024)
Teacher performance remains a central issue in early childhood education because teachers are not merely instructional agents but also emotional, social, and developmental facilitators for young children. In kindergarten settings, professional performance is shaped not only by pedagogical competence and institutional support but also by psychological factors, particularly motivation, emotional maturity, patience, and commitment to child-centred learning. This study aims to explore how psychological aspects, especially teacher motivation, support teacher performance in an Indonesian kindergarten context. Using a naturalistic qualitative approach, the study was conducted at Sakinah I Kindergarten, Sukabumi Regency, West Java, Indonesia. Data were collected through interviews, direct observation, and documentation involving kindergarten teachers and the school principal. The findings indicate that teacher performance was perceived as very good, as reflected in institutional achievements, teacher awards, sustained accreditation performance, adaptive teaching practices during the Covid-19 pandemic, and continuous communication with parents. Teacher motivation emerged through several intrinsic and prosocial dimensions, including enjoyment in teaching young children, creativity, emotional resilience, patience, meaningful relationships with pupils, and a moral sense of educational service. The study argues that motivation functions as an internal psychological resource that enables teachers to maintain performance, adapt pedagogically, and sustain emotional engagement in early childhood education. The findings contribute to discussions on teacher motivation, professional performance, and educational quality in early childhood institutions, particularly in under-researched local Indonesian contexts.